The Correlation between the Determination of Vaginal Micro-Ecological Composition and the Outcome of HPV Infection by High-Throughput Metagene Sequencing Information Technology on the Illumina Platform. Issue 12 (December 2020) - Cheng, Weiye; Xu, Fei; Gao, Leilei; Liu, Jinwei
Abstract: Objective: To study the correlation between vaginal micro-ecological composition and the outcome of human papillomavirus (HPV) infection by High-Throughput Metagene Sequencing Information Technology on the Illumina Platform, and to improve the efficiency of clinical infection detection. Methods: With the aid of Illumina high-throughput sequencing platform and sequence research method, the composition and diversity of vaginal microorganisms in high-risk HPV (HR-HPV) infected women and healthy women were analyzed. The differences in vaginal flora of HR-HPV infected women and healthy women were compared to explore the correlation between HR-HPV infection and vaginal flora. Results: The structure of vaginal flora in healthy women was relatively single, with Lactobacillus as the dominant genus, accounting for more than 80%. The structure of vaginal flora in women infected with HR-HPV was significantly different from that in non-infected women. The former had a significantly increased species diversity, which was mainly manifested by a decrease in Lactobacillus and an increase in Gardnerella vaginalis. Mycoplasma and Ureaplasma urealyticum might play a synergistic role in the initial stage of cervical lesions caused by HR-HPV infection. Conclusion: The prevention and treatment of mycoplasma and Ureaplasma urealyticum should be valued clinically to prevent the occurrence of HR-HPV infection and cervical lesions.